RELOKASI YANG DIMINTA : PELAKSANAAN RELOKASI DALAM PERSPEKTIF KEWARGANEGARAAN (Studi Kasus: Masyarakat Dusun Tambaksari dan Dusun Senik Desa Bedono Kecamatan Sayung Kabupaten Demak) - R .; Teguh Yuwono (Journal of Politic and Government Studies, 2019)
The relocation policy carried out on residents in Tambaksari Hamlet and Senik Hamlet, Bedono Village, Sayung Subdistrict, Demak Regency was one of the relocation policies caused by the rob disaster that hit the two hamlets. Where there are groups of citizens who accept and reject the relocation policy. The main purpose of implementing the relocation policy is for the safety of citizens. In this study the authors aimed to determine the impact other than safety that existed in the community after the relocation policy was implemented starting from the social and cultural fields, political fields, economic fields, and environmental fields. Where the existing implementation is also seen in the perspective of citizenship through its four dimensions, namely membership, legal status, rights, and participation. The research method used is descriptive qualitative with data collection techniques in the form of interviews and observations. The results of this study indicate that there is a fact that the relocation policy implemented is based on community demand. Then the implementation of relocation is felt by the recipient and the refusal to address the conditions that are in harmony with the dimensions of citizenship, namely in the dimensions of Legal Status, Rights and Participation. Meanwhile, there is one post-relocation condition that is contrary to the dimension of citizenship, namely in its membership dimension. Keywords: impact, relocation, citizenship